Patient and public involvement in randomised controlled trials in general and abdominal SURGery: a protocol for the PPISurg systematic review - Seiboldt, Till; Holze, Magdalena; Kalkum, Eva; Joos, Maximilian; Merz, Daniela; Vey, Johannes; Awounvo Awounvo, Junior Sinclair; Tenckhoff, Solveig; Klotz, Rosa (BMJ open, 2025)
Introduction Randomised controlled trials (RCTs) are central to generating high-quality evidence in the surgical field but face unique methodological and practical challenges, including recruitment, follow-up, blinding and ensuring patient-centred outcomes. Patient and public involvement (PPI) has emerged as a promising strategy to enhance the relevance, quality and impact of surgical research by actively involving patients throughout the whole research process. Despite growing recognition of its value, the integration and reporting of PPI in surgical RCTs remain inconsistent, and no systematic evaluation has yet addressed its application within general and abdominal surgery. - Methods and analysis RCTs in general and abdominal surgery published since 2014 will be identified through systematic searches of the databases MEDLINE, Web of Science and CENTRAL. This systematic review and primary (meta-epidemiological) statistical analysis will assess the reporting prevalence, implementation extent and quality of PPI over time. The Guidance for Reporting Involvement of Patients and the Public 2 (GRIPP2)-SF checklist and Cochrane Risk of Bias V.2.0 tool will be used to evaluate PPI reporting and study quality. To enable a comparison between studies reporting PPI and those that do not, propensity score matching will be performed to identify non-PPI studies with similar population and design characteristics. Subsequently, regression analyses will be employed to investigate potential associations between PPI reporting and various trial characteristics, including patient recruitment and retention, outcome selection and methodological quality. The Patient Advisory Board of the Study Centre of the German Society of Surgery is actively engaged in all phases of the systematic review. - Ethics and dissemination This systematic review does not require ethical approval. Results will be published in an international peer-reviewed scientific journal, as well as distributed in a lay format to the patient community and to the broader public. - PROSPERO registration number CRD42024524426.
Gesehen am 24.02.2026